Inhibition of tumor necrosis factor alpha and increased of interleukin 10 by Lactobacillus: a molecular mechanism protection against TNBS-induced ulcerative colitis in chicks. (2nd January 2019) - Jing, Long; Yu, Zhiqiang; Gao, Xueli; Liu, Chaonan; Lv, Xiaoping; Zheng, Shimin
Abstract: The purpose of this study was to evaluate the effects and mechanism of Lactobacillus on ameliorating ulcerative colitis chicks induced by 2, 4, 6-trinitrobenzene sulfonic acid (TNBS). There are three groups in this study, control, Lactobacillus and ulcerative colitis groups. 1-day-old chicks were fed with microcapsules containing Lactobacillus LA-5 daily for Lactobacillus group and clustered with 2, 4, 6-trinitrobenzene sulfonic acid (TNBS) to make the model of ulcerative colitis at ten-day-old. Chicks in control and ulcerative colitis groups were fed with empty microcapsules daily at 1-day-old and then chicks in ulcerative colitis group were induced by 2, 4, 6-trinitrobenzene sulfonic acid (TNBS) for preparation of ulcerative colitis model at 10-day-old. We detected the changes of mRNA and protein expression of TNF-α and IL-10 in the colon by Real-Time PCR and Western Blot. Histopathology evaluation on colon was conducted. Results showed that chicks pretreated with Lactobacillus had striking injury improvement compared with ulcerative colitis group in histopathology. Compared with ulcerative colitis group, down-regulation of TNF-α and up-regulation of IL-10 were observed in Lactobacillus group chicks. Therefore, Lactobacillus could improve the injury of intestinal mucosa and reduce inflammatory response by regulating mRNA and protein expression levels of TNF-α and IL-10, respectively. In conclusion, Lactobacillus could ameliorate the effects on chicks of TNBS-induced ulcerative colitis by reducing the inflammation and regulating the expression of TNF-α and IL-10, respectively.